The Effect of a pompage protocol on hemodynamic behavior during and on isometric exercise recovery in elderly: randomized and controlled study: RANDOMIZED AND CONTROLLED STUDY - Dezani, Gabrielle Varejano; Teles, Stephanny Nascimento; Ribeiro, Beatriz Pinheiro; Moreira, Leila Dal Poggetto; Viscardi, Luciana Gonzales Auad; Martins, Edmara AP Reis; de Oliveira, Adriana Sarmento (Manual Therapy, Posturology & Rehabilitation Journal, 2022)
The aging process is associated with changes in hemodynamic control, such as reduced sensitivity of baroreceptors. Advanced evidence that some manual therapies, expanded physiotherapy specialty in the treatment of basic musculoskeletal disorders, be complementary to physical exercises performed in cardiovascular rehabilitation, studies that are very scarce in this area in Brazil. Objective: to evaluate the effect of a pomping protocol on hemodynamic behavior during isometric exercise in the elderly. Methodology: A prospective randomized controlled interventional study was carried out. 503 elderly people were initially screened, of which 70 elderly were selected to participate in two randomized sessions held on different days: one with a pomping protocol based on Bienfait (1999) and another with a placebo protocol, totaling 140 transactions. The behavior of blood pressure (BP) and heart rate (HR) at rest for 5 minutes and then during three minutes of isometric exercise with handgrip (EH101, Camry) at 30% of the maximum voluntary contraction were adopted. Afterwards, the pompage protocol or randomized placebo was treated for that specific session for 30 minutes and immediately after intervention/placebo they were repeated as calculated grouping. Results: The elderly had a mean age of 69 ± 1.0 years. Regarding BP values (SBP,131±1.4 mmHg; DBP=83±1.6 mmHg), it is possible to observe that most of the elderly were classified as pre-hypertensive, according to the Brazilian Guidelines on Arterial Hypertension. (2020). We emphasize that there was a reduction in SBP only in the pompage group (p < 0.001), a reduction in DBP only in the pompage group in the first minute (p=0.03) and in the third minute (p=0.04) and a reduction in HR in both groups (p < 0.001 and p = 0.02). Conclusion: The pompagens protocol reduced the SBP of the elderly during isometric exercise with the handgrip and the DBP in the recovery from isometric exercise, while there was no change in SBP in the placebo group during isometrics and no change in DBP in the placebo group during recovery from isometric exercise.